1987
DOI: 10.1111/j.1600-0897.1987.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Lymphocyte Activation by a High‐Molecular‐Weight Glycoprotein Released From Preimplantation Ovine and Porcine Conceptuses

Abstract: A high-molecular-weight (MW greater than 660,000), acidic glycoprotein (HMWGP) was purified from incubation medium of preimplantation, elongating ovine (day 16 and 17) and porcine (day 16) conceptuses. HMWGP was tested for its ability to inhibit [3H-methyl]thymidine incorporation into lymphocytes stimulated by phytohemagglutinin or two-way mixed lymphocyte cultures. Ovine and porcine HMWGP inhibited the incorporation of [3H-methyl]thymidine into lymphocytes in a dose-dependent manner. An approximately 50% inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Proteinaceous products from extraembryonic membranes have been reported to have thyrotropic (Avivi et al, 1982), luteotropic (Ailenberg and Shemesh, 1983), antiprostanoid (Shemesh et al, 1984;Knickerbocker et al, 1986), lactogenic (Bolander and Fellows, 1976;Beckers et al, 1980;Eakle et al, 1982;Murthy et al, 1982), and immunosuppressive (Murray et al, 1987) activities. Clearly, conceptus proteins may function as important hormones in the establishment, maintenance, and regulation of pregnancy.…”
Section: Ntr Od Uct I0 Nmentioning
confidence: 96%
“…Proteinaceous products from extraembryonic membranes have been reported to have thyrotropic (Avivi et al, 1982), luteotropic (Ailenberg and Shemesh, 1983), antiprostanoid (Shemesh et al, 1984;Knickerbocker et al, 1986), lactogenic (Bolander and Fellows, 1976;Beckers et al, 1980;Eakle et al, 1982;Murthy et al, 1982), and immunosuppressive (Murray et al, 1987) activities. Clearly, conceptus proteins may function as important hormones in the establishment, maintenance, and regulation of pregnancy.…”
Section: Ntr Od Uct I0 Nmentioning
confidence: 96%
“…Investigations have not yet defined the mechanism(s) responsible for the immunological survival of the ovine conceptus. It is apparent that the progesterone (P4)-treated, ovariectomized ewes have been shown to suppress in vitro T-lymphocyte proliferation in mitogen-treated, interleukin-2 (IL-2)-treated, and mixed-lymphocyte cultures (Segerson, 1981(Segerson, , 1988Staples et al, 1983;Hansen et al, 1986Hansen et al, , 1987Murray et al, 1987;Newton et al, 1989;Niwano et al, 1989;Stephenson et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Roth et al (1991) have shown that this suppressor factor, horse conceptus-derived immunosuppressive factor (HCS) has M, > 100 000. High Mr components of cultures of conceptuses and of gravid uterine fluid of other domestic species, such as cows (Segerson & Bazer, 1989), sheep Murray et al, 1987) and pigs (Murray et al, 1987), also suppress lymphocytes when used to supplement blastogenesis cultures in vitro. These suppressive factors may play a role in protecting the conceptus from maternal immunological attack during pregnancy.…”
Section: Introductionmentioning
confidence: 99%